TINJAUAN YURIDIS KONSEP MAKAR DALAM PERSPEKTIF HUKUM TATA NEGARA ISLAM - Alam, Syariful (Faculty of Law, University of Muhammadiyah Malang, 2018)
The treason or treason act is closer to the act of betrayal. In a constitutional law perspective, this treason is defined as the act of a person or group of people towards leadership in a country because of its incompatibility with the rules that apply in the country, so that he or they take actions that tend to